Clinical manifestations of children with COVID‐19: A systematic review - Souza, Tiago H.; Nadal, José A.; Nogueira, Roberto J. N.; Pereira, Ricardo M.; Brandão, Marcelo B. (Pediatric pulmonology, 2020)
Background The coronavirus disease 2019 (COVID‐19) outbreak is an unprecedented global public health challenge, leading to thousands of deaths every day worldwide. Despite the epidemiological importance, clinical patterns of children with COVID‐19 remain unclear. The aim of this study was to describe the clinical, laboratorial, and radiological characteristics of children with COVID‐19. Methods The Medline database was searched between December 1st 2019 and April 6th 2020. No language restrictions were applied. Inclusion criteria were (a) studied patients younger than 18 years old; (b) presented original data from cases of COVID‐19 confirmed by reverse‐transcription polymerase chain reaction; and (c) contained descriptions of clinical manifestations, laboratory tests, or radiological examinations. Results A total of 38 studies (1124 cases) were included. From all the cases, 1117 had their severity classified: 14.2% were asymptomatic, 36.3% were mild, 46.0% were moderate, 2.1% were severe, and 1.2% were critical. The most prevalent symptom was fever (47.5%), followed by cough (41.5%), nasal symptoms (11.2%), diarrhea (8.1%), and nausea/vomiting (7.1%). One hundred forty‐five (36.9%) children were diagnosed with pneumonia and 43 (10.9%) upper airway infections were reported. Reduced lymphocyte count was reported in 12.9% of cases. Abnormalities in computed tomography were reported in 63.0% of cases. The most prevalent abnormalities reported were ground‐glass opacities, patchy shadows, and consolidations. Only one death was reported. Conclusions Clinical manifestations of children with COVID‐19 differ widely from adult cases. Fever and respiratory symptoms should not be considered a hallmark of COVID‐19 in children.